Analysis of the fine structure of the D-exciton shell in cuprous oxide - Heckötter, Julian; Rommel, Patric; Main, Jörg; Aßmann, Marc; Bayer, Manfred (Technische Universität Dortmund, 2021)
The exciton states in cuprous oxide show a pronounced fine structure splitting associated with the crystal environment and the resulting electronic band structure. High-resolution spectroscopy reveals an especially pronounced splitting of the yellow D excitons with one state pushed above any other state with the same principal quantum number. This large splitting offset is related to a strong mixing of these D states with the 1S exciton of the green series, as suggested by previously published calculations. Here, a detailed comparison of this theory with experimental data is given, which leads to a complete reassignment of the experimentally observed D exciton lines. The origin of different amounts of green admixture to D-envelope states is deduced by analyzing the different terms of the Hamiltonian. The yellow–green mixing leads to level repulsion and induces an exchange interaction splitting to D-envelope states, from which one of them becomes the highest state within each multiplet. Furthermore, the assignment of D exciton states according to their total angular momentum F is given and corrects an earlier description given in a former study.
Physica status solidi. Rapid research letters;15(11)
Keywords: High-resolution spectroscopy; Rydberg excitons; Semiconductors; 530